2020
DOI: 10.1136/gutjnl-2019-319984
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage repair as a target in pancreatic cancer: state-of-the-art and future perspectives

Abstract: Complex rearrangement patterns and mitotic errors are hallmarks of most pancreatic ductal adenocarcinomas (PDAC), a disease with dismal prognosis despite some therapeutic advances in recent years. DNA double-strand breaks (DSB) bear the greatest risk of provoking genomic instability, and DNA damage repair (DDR) pathways are crucial in preserving genomic integrity following a plethora of damage types. Two major repair pathways dominate DSB repair for safeguarding the genome integrity: non-homologous end joining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 127 publications
(140 reference statements)
2
90
0
2
Order By: Relevance
“…On the other hand, during treatment induced tumor evolution, DDR sufficient cancer cells can outgrow the DDR deficient tumor clones, thus leading to the development of treatment resistance. MRN complex (MRE11, RAD50 and NBN) is the initial core of DNA double-strand breaks (DSB) repair machinery, while PALB2, RAD51 among several other key regulators contribute to the later stages of DDR [47] . Our study identifies the enrichment of several key regulators of DDR in m6Ascore-high tumors, indicating a potential link between m6A, DDR, and immune evasion in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, during treatment induced tumor evolution, DDR sufficient cancer cells can outgrow the DDR deficient tumor clones, thus leading to the development of treatment resistance. MRN complex (MRE11, RAD50 and NBN) is the initial core of DNA double-strand breaks (DSB) repair machinery, while PALB2, RAD51 among several other key regulators contribute to the later stages of DDR [47] . Our study identifies the enrichment of several key regulators of DDR in m6Ascore-high tumors, indicating a potential link between m6A, DDR, and immune evasion in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, BRCA1 or BRCA2 are not the most frequently mutated DDR genes in sporadic PDAC in a general Western population. ATM is mutated in up to 5% of sporadic PDAC 13 and operates as a key enzyme in homologous recombination (HR) repair, mounting a bona fide HR-defective (HRDness) 14 model for PDAC. 15 Our group previously showed that ATM deficiency, even on heterozygous deletion, causes metastatic and aggressive PDAC undergoing epithelial-mesenchymal transition (EMT), negatively impacting prognosis in humans and mice.…”
Section: Pancreasmentioning
confidence: 99%
“…[25,27,28] Moreover, H2AX had been proved to be involved in cancer initiation and progression. [29,30] Also, H2AX plays a vital role in regulating tumor cell proliferation [31] and angiogenesis. [32]…”
Section: Discussionmentioning
confidence: 99%